Keluhan Subjektif Fotokeratitis Akibat Paparan Sinar UV pada Pekerja Las di PT. X - Khusnul Khotimah; Endang Dwiyanti (Universitas Airlangga, 2023)
Background: Eye injuries can result from sparks produced during welding. Photokeratitis, commonly known as welders flash, is one of the eye injuries that commonly affect welders. At least half of all accidents and suffering that have happened have been caused by photokeratitis, an eye injury that frequently results in decreased vision. Objectives: Finding out the general picture of subjective complaints of photokeratitis among welders at PT. X. Methods: A cross sectional technique was used to conduct this investigation in an analytical observational approach. The participants in this study were all PT. X welders. The complete population, or as many as 27 welders, serves as the study's sample. Data processing is carried out with software SPSS 18 which is then carried out descriptive analysis with frequency distribution tables. Results: Based on the criteria for classifying cases according to photokeratitis symptoms, it can be seen that, out of a total of 27 welding workers, 19 respondents (70.4%) are categorized as experiencing subjective complaints of photokeratitis, while the remaining 8 respondents (29.6%) are not included in the criteria for experiencing subjective complaints of photokeratitis. Conclusions: Based on the results The majority of the welders at PT. X reportedly complained of subjective photokeratitis.